2016
DOI: 10.1080/13875868.2016.1166229
|View full text |Cite
|
Sign up to set email alerts
|

Navigation in outdoor environments as an embodied, social, cultural, and situated experience: An empirical study of orienteering

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 52 publications
0
8
0
1
Order By: Relevance
“…Therefore, access to pre-reflexive consciousness provides a disclosure of the world as meaningfully experienced by the agent. Furthermore, within the sports psychology literature, the course-of-action framework has already been used to gain insight into performance in many sports like trampoline and acrobatics (Hauw and Durand, 2004, 2008), skydiving (Mohamed et al, 2015), table tennis (Sève et al, 2005), orienteering (Mottet et al, 2016), rowing (Sève et al, 2013), soccer (Villemain and Hauw, 2014; Gesbert et al, 2017), and trail running (Antonini Philippe et al, 2016; Hauw et al, 2017; Rochat et al, 2017). All these studies analyzed embedded activity through activity analysis and were able to provide practical recommendations for training, education, and competition (e.g., Hauw, 2017, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, access to pre-reflexive consciousness provides a disclosure of the world as meaningfully experienced by the agent. Furthermore, within the sports psychology literature, the course-of-action framework has already been used to gain insight into performance in many sports like trampoline and acrobatics (Hauw and Durand, 2004, 2008), skydiving (Mohamed et al, 2015), table tennis (Sève et al, 2005), orienteering (Mottet et al, 2016), rowing (Sève et al, 2013), soccer (Villemain and Hauw, 2014; Gesbert et al, 2017), and trail running (Antonini Philippe et al, 2016; Hauw et al, 2017; Rochat et al, 2017). All these studies analyzed embedded activity through activity analysis and were able to provide practical recommendations for training, education, and competition (e.g., Hauw, 2017, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…For example, studies have revealed that pressure will influence orienteers’ performances of memory (Robazza et al, 2018) and attention (Eccles, Walsh & Ingledew, 2006) in map reading in running. Moreover, attention shifts between the map and the environment (Mottet, Eccles & Saury, 2016; Pesce et al, 2007) will influence the visual search patterns of novice and expert orienteers and the result of the competition. Therefore, time and space can be introduced in future studies to improve their authenticity and thus improve ecological validity.…”
Section: Discussionmentioning
confidence: 99%
“…section 6 of the protocol). Lastly, this specific interview and its analysis are time-consuming and limit the number of participants in the mixed methods; studies with the enactive phenomenological framework usually have an number of participants between 4 and 13 14,15,18,19,20,27,49,50,51 . This particularity of in-depth qualitative research with case studies raises the question of generalization of the results.…”
Section: Copyright © 2018 Journal Of Visualized Experimentsmentioning
confidence: 99%